Gambaran medication error pada fase prescribing dan administrasi pada pengobatan stroke di Igd rumah sakit X di Yogyakarta - Tomi; Akrom; Agnes Jatiningrum (Universitas Ahmad Dahlan, 2017)
Stroke is widely known as an emerging disease that which requires quick and precise treatment in the emergency department (ED) of hospital. This study aims to determine the number of ER of Hospital X. An observational study througha prospective analysis of ER was conducted from December 2014 to April 2015. Herein, weobtained a total of 106 patients with inclusion subject criterions,includingpatients with non-hemorrhagic stroke and patients with hemorrhagic stroke diagnosis, where both are either withor without comorbidities. Data processing was done through Monovariate analysis to describe the general characteristics of the patients, clinical descriptionof patients, depictionof the incidence, distribution, and ME phase. The description, distribution of the incidence data, and ME phase were presented in percentage subsequently.This study resulted that the number of geriatric patients over than 60 years old were 67 patients (63.20%). Both patients criterions, who are with the non-hemorrhagic and with the hemorrhagic strokes, were recorded to be 85.80% and 14.20%, respectively. While, MEs occurred in 104 patients or 98.1% of all participants. The distributions of MEs in the phases of the prescribing and administration per patient were 28 who experienced once ME incidence, 48 who experienced two times ME incidences, 20 patients who experienced three episodes ME incidences, and 8 patients experienced with four times ME incidences. The total incidences of ME were 216 obtained from the 106 patients with an average value was 2 per patient. Furthermore, MEs in prescribing and administration phases were reported to be 98.11% and 61.32%, respectively.